Traumatic stress in emergency nurses: Does your work environment feel like a war zone?. (September 2020) - Wolf, Lisa A.; Delao, Altair M.; Perhats, Cydne; Clark, Paul R.; Edwards, Courtney; Frankenberger, Warren D.
Highlights: Emergency nurses in this sample report high levels of secondary traumatic stress. Trauma is cumulative. Participants reported high levels of suicidality in themselves and their colleagues. Social support is beneficial in mitigating work-related traumatic stress. High levels of traumatic stress may impede the recognition of patient decompensation or patient behavioural escalation cues. Abstract: Introduction: Emergency nurses are exposed to both primary and secondary trauma with attendant sequelae in both work and personal spheres. The purpose of the study was to investigate the prevalence of traumatic stress, measured by the secondary traumatic stress scale (STSS) in a sample of emergency nurses and describe the impact of traumatic stress on nursing practice and workplace environment. Methods: Mixed methods approach using survey instrument data from the Secondary Traumatic Stress Scale (STSS) (N = 125) and focus group data (N = 53). Results: The average total score on the STSS was 51.83 for nurses who attended one of the focus groups 48.42 for nurses who did not attend (clinical cutoff for STS = 39). Focus group data aligned with elements of the STSS; thematic categories of cumulative trauma, mental health sequelae, bullying and organizational violence, coping mechanisms, relationship damage, and solutions were described. Although we measured only STS, participants often used the terms "PTSD" and "STS" interchangeably. Conclusions: The nurses in this study demonstrated high levels of STS and described in detail how chronic, cumulative trauma affected relational nursing care and social connections. Participants discussed high levels of suicidality in the profession, and the compounding trauma of relational and organizational violence. The pervasiveness of traumatic stress and the extent to which it affects all areas of nurses' lives is a cause for great concern.